The impact of a didactic and experiential learning model on health profession students' knowledge, perceptions, and confidence in the use of telehealth - Karene Boos; Kerri Murphy; Thomas St George; James Brandes; Jane Hopp (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Training of health profession students in telehealth is important to ensure proper implementation for healthcare delivery. This prospective study aimed to analyze the effects of didactic and experiential learning on knowledge, confidence, and attitudes of telehealth among health profession students (Survey 1). The perceptions of a mixed model telehealth platform were also considered among these students and community clients (Survey 2). MATERIALS AND METHODS: A quasi-experimental repeated-measure study was conducted on 153 university health profession students in physician assistant, physical therapy, occupational therapy, and nursing (NR) across the 2020-2021 academic year. Survey 1 was administered to students pre/postdidactic telehealth training and at two sequential points within two semesters of telehealth experiential learning. Survey 2 was distributed among students and a pool of 19 community clients at 4 time points across the experience. Survey data were analyzed using R software. RESULTS: There was a significant improvement in telehealth knowledge, confidence, and attitudes among all student disciplines after the didactic module with marginal means ranging 3.313/5-4.318/5 for pretest to posttest 1. Improvement continued through experiential learning with marginal means ranging 4.170/5-4.369/5 in posttest 3. There was also a significant student and client approval of the telehealth platform with a student mean high of 3.962/5 ± 0.527 and client mean high of 4.727/5 ± 0.238. CONCLUSION: A didactic training module combined with experiential learning is effective for health profession students' improvement in perception, knowledge, and attitudes toward telehealth. Health profession students and community clients approve a mixed model telehealth platform.